Dissecting the role of the gut microbiome and fecal microbiota transplantation in radio- and immunotherapy treatment of colorectal cancer - Van Dingenen, Lena; Segers, Charlotte; Wouters, Shari; Mysara, Mohamed; Leys, Natalie; Kumar-Singh, Samir; Malhotra-Kumar, Surbhi; Van Houdt, Rob (Frontiers in Cellular and Infection Microbiology, 2023)
Colorectal cancer (CRC) is one of the most commonly diagnosed cancers and poses a major burden on the human health worldwide. At the moment, treatment of CRC consists of surgery in combination with (neo)adjuvant chemotherapy and/or radiotherapy. More recently, immune checkpoint blockers (ICBs) have also been approved for CRC treatment. In addition, recent studies have shown that radiotherapy and ICBs act synergistically, with radiotherapy stimulating the immune system that is activated by ICBs. However, both treatments are also associated with severe toxicity and efficacy issues, which can lead to temporary or permanent discontinuation of these treatment programs. Increasing evidence suggests that the gut microbiome contributes to these issues, with some microbial members contributing to radiotherapy-associated toxicity and ICB efficacy, while other members appear to reduce radiotherapy-associated toxicity or enhance ICB efficacy. Consequently, fecal microbiota transplantation (FMT) has been applied to reduce radio-and immunotherapy-related toxicity and enhance their efficacies. Here, we have reviewed the currently available preclinical and clinical data in CRC treatment, with a focus on how the gut microbiome influences radio-and immunotherapy toxicity and efficacy and if these treatments could benefit from FMT.